2011
DOI: 10.1073/pnas.1112849108
|View full text |Cite
|
Sign up to set email alerts
|

Large-area optoelastic manipulation of colloidal particles in liquid crystals using photoresponsive molecular surface monolayers

Abstract: Noncontact optical trapping and manipulation of micrometer-and nanometer-sized particles are typically achieved by use of forces and torques exerted by tightly focused high-intensity laser beams. Although they were instrumental for many scientific breakthroughs, these approaches find few technological applications mainly because of the small-area manipulation capabilities, the need for using high laser powers, limited application to anisotropic fluids and low-refractive-index particles, as well as complexity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 46 publications
2
80
0
Order By: Relevance
“…Future studies will also explore dynamics of nucleation and annihilation of defects as particles are continuously rotated by external magnetic and optical torques, the influence of elastic constant anisotropy on the stability of different stable and metastable configurations, and hysteresis in switching between different states, as well as how spatial localization of boojums is related to intrinsic curvature of colloidal surfaces. The experimental arena we have developed, combined with the ability to achieve optical control of surface anchoring on colloidal surfaces (40) and the use of chiral LCs (7), may become a test ground for applying and probing a number of newly developed theories describing the topology of nematic defects, such as the CoparZumer theory (41), and may be extended to topologically nontrivial LC confinement geometries (12).…”
Section: Resultsmentioning
confidence: 99%
“…Future studies will also explore dynamics of nucleation and annihilation of defects as particles are continuously rotated by external magnetic and optical torques, the influence of elastic constant anisotropy on the stability of different stable and metastable configurations, and hysteresis in switching between different states, as well as how spatial localization of boojums is related to intrinsic curvature of colloidal surfaces. The experimental arena we have developed, combined with the ability to achieve optical control of surface anchoring on colloidal surfaces (40) and the use of chiral LCs (7), may become a test ground for applying and probing a number of newly developed theories describing the topology of nematic defects, such as the CoparZumer theory (41), and may be extended to topologically nontrivial LC confinement geometries (12).…”
Section: Resultsmentioning
confidence: 99%
“…Elastic properties of LCs trigger anisotropic interactions between colloids, [1][2][3][4][5][6] directing their self-assembly into macrostructures [7][8][9][10][11][12][13][14] useful, for example, in photonics applications. [11][12][13] During the last decades, experimental and theoretical studies covered different aspects of elastic interactions between spherical colloids mostly in nematic LCs.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] During the last decades, experimental and theoretical studies covered different aspects of elastic interactions between spherical colloids mostly in nematic LCs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Two- [7][8][9][10][11] and three-dimensional 14 crystals were designed in nematics using different elastic dipoles and quadrupoles, and singular defects were tailored using spherical 16 and topologically non-trivial 17 colloidal particles. Recent studies also showed the importance of size [18][19][20][21][22][23][24] and shape [24][25][26][27][28][29][30][31] in elastic interactions and ensuing assemblies of colloidal particles in nematics.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, equation (10) implies that the interfacial deformation in the limit qw p → 0 has the scaling form…”
Section: A Scaling Function For H(x)mentioning
confidence: 99%
“…Apart from an academic interest, a fundamental understanding of such systems will pave the way for the design and manufacturing of novel materials, devices, and applications. Examples include smart surfaces with self-cleaning [7], enhanced heat transfer [8], reduced fluid drag [9] or photo-responsive properties [10]; templatedirected assembly of colloidal particles [11][12][13]; microfluidics [14,15] and optofluidics [16][17][18].…”
Section: Introductionmentioning
confidence: 99%